Behavioral Patterns of Local Communities in Responding to Climate Change Challenges in Tourism in the Seribu Islands - Vera Inne Juni Simamora; Annisa Husnul Latifah; Yudha Wangsah (Ilomata International Journal of Social Science, 2026)
Global climate change has had a significant impact on the tourism sector, particularly in marine destinations that depend on the stability of coastal ecosystems. The Seribu Islands, as one of Indonesia’s prime tourism destinations, face serious threats such as sea-level rise, coastal erosion, ecosystem degradation, and an increased frequency of tidal flooding, all of which have implications for both environmental and economic sustainability of local communities. This study aims to identify and analyze the adaptive behavioral patterns of local communities in responding to climate change challenges to tourism. The research employed a qualitative approach with a case study design in four inhabited islands (Tidung, Pramuka, Pari, and Kelapa). Informants were selected through purposive sampling and included homestay owners, tour guides, tourism-related MSME actors, marine transport providers, community leaders, and environmental activists. Data were collected through in-depth interviews, participatory observation, and document analysis, and subsequently analyzed using thematic analysis. The findings reveal that local communities apply adaptation strategies across three main dimensions: (1) economic, through business diversification, digital innovation, and the utilization of local resources; (2) environmental, through ecosystem conservation, participatory waste management, and the efficient use of energy and water; and (3) socio-institutional, through collective action, strengthening of social networks, and collaboration with government, universities, and NGOs. These results underscore that successful adaptation is determined by the integration of economic, environmental, and social aspects, and is not uniform across the islands, with Pramuka Island demonstrating greater preparedness compared to the others. This research provides important implications for sustainable tourism development policies that are adaptive to climate change, emphasizing the need for policy support, institutional capacity building, and community participation in maintaining socio-ecological resilience in coastal areas. Climate Change, Tourism, Community Behavior, Adaptation Strategies, Seribu Islands